Home-monitoring/remote optical coherence tomography in teleophthalmology in patients with eye disorders—a systematic review - Dolar-Szczasny, Joanna; Drab, Agnieszka; Rejdak, Robert (Frontiers in Medicine, 2024)
Teleophthalmology uses technology to provide remote eye care services, tackling obstacles in accessing specialized care. Optical coherence tomography (OCT) represents a technical advancement, enabling high-resolution ocular imaging. The aim of this study is to evaluate the diagnostic accuracy, feasibility, safety, and clinical utility of home monitoring OCT devices and remote OCT technology compared to standard in-office OCT in teleophthalmology settings across various eye conditions.A systematic literature search was conducted in PubMed, Cochrane Library, ScienceDirect and Google Scholar for studies on home-monitoring/remote OCT published from January 2004 to February 2024. Studies utilizing home monitoring/remote OCT in teleophthalmology for patients with eye disorders and reporting on diagnostic accuracy, safety, disease monitoring (clinical utility) or treatment response were included and synthesized narratively. Results A total of 12 research studies involving 3539 participants were incorporated in the analysis. The majority of home or remote OCT scans exhibited satisfactory diagnostic image quality. There was high agreement between home/remote and in-office OCT for detecting pathologies and measuring retinal thickness. Compared to in-person evaluations, home/remote OCT demonstrated excellent sensitivity and specificity, though some variability was seen across conditions and interpreters. Home OCT devices provided feasible and safe self-operation with high patient acceptability. Scan times were faster when conducted at home compared to those in the office.Home/remote OCT devices can effectively provide diagnostic-grade retinal imaging outside traditional settings. High diagnostic accuracy was demonstrated compared to in-office OCT. Feasibility and patient acceptability data support home OCT for remote monitoring.